Integrating Sufi Values in Aceh’s Dayah Salafiyah: Strategies and Challenges in Harmonizing Tradition with Modernity - Wildan, Raina; Marwan, Ade Zahara; Zulfian, Zulfian; Marzuki, M. Fathin Shafly; Mazlan, Muhamad Fakarudin Bin (Jurnal Pemikiran Islam, 2024)
Dayah Salafiyah in Aceh play a crucial role in preserving Islamic traditions and instilling Sufi values, particularly in the face of modernization and technological advancement. These institutions focus on developing ethical and spiritual resilience among students while addressing challenges posed by contemporary societal changes. This study investigates the methods employed by Dayah BUDI Mesja Lamno, Dayah Darul Munawwarah Kuta Krueng, Dayah MUDI Mesra Samalanga, and Dayah Ruhul Fata Seulimum Aceh Besar to internalize and adapt Sufi values in their educational frameworks. Using a qualitative approach, data were collected through interviews, direct observations, and curriculum analysis. The study found that dayahs utilize methods such as the study of kitab turath, spiritual retreats (khalwat), daily rituals, and mentorship to foster virtues like humility, patience, and reliance on God. However, challenges persist, including technological distractions, societal pressures, and misconceptions about Sufism. The dayahs address these through strict discipline, critical engagement, and community support. The findings affirm the enduring relevance of Sufi values in navigating modern complexities while maintaining spiritual depth. By integrating traditional teachings with selective adaptation, Dayah Salafiyah provide a balanced model for education.